Aims To Increase Civics Activity and Learning Outcomes Through the Use of Team Game Tournament Methods on Senior High School Student - Julianti; Nani Mediatati; Yosaphat Haris Nusarastriya (Graduate Program Magister Manajemen Pendidikan, 2023)
This research aims to increase student activity and learning outcomes using the Team Game Tournament (TGT) method in Civics subjects in class XII ATPH SMK Negeri 3 Salatiga. The issues of this study amounted to 36 students. Data collection techniques were observation and tests, while data analysis techniques used comparative descriptive techniques. The results obtained from this study indicate that the TGT learning method can increase student activity and learning outcomes in Civics subjects. This is evident from the average increase in student learning activeness in the first cycle of the 1st meeting 47.23% (17 students) in the 2nd meeting 69.44% (25 students), then increased in the second cycle of the 1st meeting 80, 56% (29 students) to 91.66% (33 students) at the 2nd meeting. Student learning outcomes also increased in each cycle. Pre-cycle 13.89% (5 students) who scored KKM ≥ 77 increased to 77.78% (28 students) in cycle I, and rose again to 94.44% (34 students) in cycle II. Based on the results of this study, it can be concluded that using the TGT method can increase the activity and learning outcomes of civics subjects’ students of class XII ATPH SMK Negeri 3 Salatiga.